A new microwave-assisted, three-component reaction of 5-aminopyrazole-4-carboxylates:selective synthesis of substituted 5-aza-9-deaza-adenines - Lim, Felicia Phei Lin; Halcovitch, Nathan R.; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Elsevier, 2018)
annulation of 1,3,5-triazine ring onto 5-aminopyrazole-4-carboxylates via a one-pot,multicomponent, microwave-assisted approach. The products were obtained in good yields and high purity. This catalyst-free method was demonstrated to be scalable and highly reproducible in different microwave reactors. Some structural features of the prepared compounds were studied in details using dynamic NMR spectroscopy and X-ray crystallography.